Promotion of ATP and S-140 to ribosome inactivation with camphorin, cinnamomin, and other RNA N-glycosidases - Ruan Jia-Peng; Chen Wen-Feng; Liu Wang-Yi (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of ATP and extra-ribosomal factors (S-140) on type I and type II RNA N-glycosidases in inactivating ribosome. METHODS: The activity of ATP and S-140 was determined by characterization of R-fragment in gel. An improved two-step method of cell-free protein synthesis system was used to quantitate the requirements of S-140 in ribosome inactivation. RESULTS: IC50 ratios of camphorin, gamma-momorcharin, luffin S, luffin A, trichosanthin (type I); and ricin, ricin A-chain; cinnamonin, cinnamomin A-chain (type II) between the absence and presence of ATP and S-140 were 3108, 151, 51, 45, 15; and 47, 7, 26, 12, respectively. CONCLUSION: The ribosome-inactivating activity of type II ribosome-inactivating proteins, including intact protein and its A-chain, was promoted by ATP and S-140. Camphorin showed a significant difference from cinnamomin in need of ATP and S-140 for such promoting.